Costs of Outpatient Thyroid Surgery from the University HealthSystem Consortium (UHC) Database. (4th February 2014) - Marino, Matthew; Spencer, Horace; Hohmann, Sam; Bodenner, Donald; Stack, Brendan C.
Abstract : Objective: To compare the cost of same‐day vs 23‐hour observation outpatient thyroidectomy at US academic medical centers. Study Design: Cross‐sectional analysis of a national database. Setting: The University HealthSystem Consortium (UHC) data collected from discharge summaries. Subjects and Methods: Discharge data were collected from the first quarter of 2009 through the second quarter of 2013. The UHC database, compiled from more than 200 affiliated hospitals, was searched based on diagnosis codes for outpatient thyroid procedures. Cost data, calculated based on reported charges, were collected in addition to demographics. Comparisons were made between same‐day vs 23‐hour observation based on cost. Additional stratification was performed based on the extent of thyroidectomy. Results: During the study period, 49, 936 outpatient thyroidectomies were performed. Overnight observation (63%) was more common than same‐day discharge (37%). The overall mean cost of outpatient thyroidectomy was $5617, with a mean cost of same‐day surgery of $4642 compared with $6101 for overnight observation ( P <. 0001). When stratifying by extent of thyroidectomy, the cost of same‐day surgery was consistently lower than that for overnight observation. Conclusion: Outpatient thyroidectomy is commonly performed in the United States. It is most commonly performed on a 23‐hour overnight observation basis. Overnight stay and complications were chief among other factors associated with higher cost, independent of the type of thyroid procedure performed. In appropriately selected patients, same‐day thyroidectomy is a safe and cost‐effective alternative to overnight observation or inpatient thyroid procedures.